Effect of deglycosylation on immunoreactivity and in vitro pepsin digestibility of major cashew (Anacardium occidentale L.) allergen, Ana o 1. Issue 3 (13th February 2021) - Zaffran, Valerie D.; Gupta, Sahil; Sathe, Shridhar K.; Roper, Michael G.
Abstract : Abstract: Major cashew allergen, Ana o 1, was purified in its native form from cashew seeds and subjected to enzymatic deglycosylation using PNGase F to assess the potential role of N‐glycans in immunoreactivity. Western and dot blotting with pooled human plasma containing anticashew IgE revealed that deglycosylation increased IgE‐binding of Ana o 1. Removal of N‐glycans may have exposed previously masked Ana o 1 epitopes. Purified glycosylated and deglycosylated Ana o 1 were also subjected to in vitro pepsin digestion at pH 3.0 for 2 hr. Both glycosylated and deglycosylated Ana o 1 remained stable and reactive with IgE antibodies following digestion. Practical Application: Understanding the role of glycosylation in Ana o 1 immunoreactivity may provide insight into the potential development of hypoallergenic cashews/cashew products for sensitive individuals in the future.